Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, Reputasi Auditor, Dan Capital Intensity Terhadap Tax Avoidance - Java Mahbubillah Nibras; Sofyan Hadinata (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2020)
Taxes are one of the important sources of state income in Indonesia, but the majority of taxpayers think that taxes are an additional burden for business activities. So that many taxpayers are planning their tax obligations with tax avoidance. This study aims to test empirically the effect of profitability, leverage, company size, auditor reputation, and capital intensity on tax avoidance. This study uses manufacturing companies listed on the Sharia Stock Index (ISSI) from 2012 to 2017. The sample selection method used is purposive sampling. The sample obtained was 21 companies, so the number of observations in this study was 126. Panel data regression analysis was used in this study using the help of Eviews version 10. Based on the results of multiple linear regression, the results show that profitability and company size has a positive effect on tax avoidance, while Auditor's reputation has a negative effect on tax avoidance. As for leverage and capital, the intensity has no effect on tax avoidance.